2005
DOI: 10.1645/ge-3492-rn.1
|View full text |Cite
|
Sign up to set email alerts
|

The First Record of Dirofilaria immitis Infection in a Humboldt Penguin, Spheniscus humboldti

Abstract: Dirofilaria immitis infection is an important parastic disease in many mammals, especially canids, but has not been reported in bird hosts. Filarial worms were isolated from the lumen of the right atrium of the heart and the connective tissue of the lung of a captive female Humboldt penguin, Spheniscus humboldti, that died at a zoo in Japan. One of these worms was observed morphologically and identified as D. immitis by features such as 4 pairs of cephalic papillae, 1 pair of cervical papillae, esophagus divid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 5 publications
0
16
1
Order By: Relevance
“…Our observations, however, differ from those of Sano et al (2005) in positioning of male phasmids. Using light microscopy, the latter authors observed phasmids situated near the tail tip.…”
Section: Remarkscontrasting
confidence: 99%
See 1 more Smart Citation
“…Our observations, however, differ from those of Sano et al (2005) in positioning of male phasmids. Using light microscopy, the latter authors observed phasmids situated near the tail tip.…”
Section: Remarkscontrasting
confidence: 99%
“…For example, Murata et al (2003) and Sano et al (2005) examined D. immitis from leopards and penguins in a Japanese zoo. They reported the presence of delicate longitudinal cuticular ridges along the entire length of the body using ordinary light microscopy.…”
Section: Remarksmentioning
confidence: 99%
“…Indeed, there already is a considerable record of zoofocused mosquito study (e.g. Beier & Trpis,1981;Nolen, 2001; Derraik, 2004a,b;McGowan, 2004;Sano et al, 2005;Nelder, 2007;Adler et al, 2011;Ejiri et al, 2011;Tuten, 2011a;Tuten 2011b;Tuten et al, 2012). However, the potential of national, regional and global-level zoo networks to contribute to mosquito-monitoring efforts remains largely unutilized.…”
Section: Survelliance Potential Of Zoo and Wildlife-park Networkmentioning
confidence: 99%
“…A range of species has been recorded as succumbing to mosquito-transmitted pathogens in zoos and theme parks. Documented cases include African black-footed penguins Spheniscus demersus with avian malaria (Grim et al, 2004) and eastern equine encephalitis virus (Tuttle et al, 2005), Great gray owls Strix nebulosa with Usutu virus (Weissenböck et al, 2002), Humbolt penguins Spheiniscus humboldti with heartworms Dirofilaria immitis (Sano et al, 2005), and a Polar bear Ursus maritimus (Dutton et al, 2009) …”
mentioning
confidence: 99%
“…Pygoscelis adeliae, stomach, Ardley Island, peninsula Fildes, Rey Jorge Island, South Shetland, Antarctica (Fredes et al 2008) Pygoscelis papua, stomach, Ardley Island, peninsula Fildes, Rey Jorge Island, South Shetland, Antarctica (Fredes et al 2006 Aptenodytes patagonicus, oesophagus and stomach, Crozet Archipelago, Antarctica (Fonteneau et al 2011) Eudyptes chrysocome, proventriculus, Kerguelen Islands, Antarctica (Schmidt 1965) Pygoscelis papua, glandular stomach, King George Island, Antarctica (Diaz et al 2013) Family Onchocercidae (Leiper, 1911) Dirofilaria immitis (Leidy, 1856) Spheniscus humboldti, heart, Japan Zoo (Sano et al 2005 Spheniscus humboldti, nests, Peru (Hoogstraal et al 1985;Smith et al 2008) Ornithodoros (Alectorobius) capensis Neumann, 1901 Eudyptula minor, nests, coast of Victoria, Australia (Kohls 1957;Murray et al 1991) Spheniscus demersus, nests, islands off Cape Province, South Africa (Kohls 1957;Hoogstraal et al 1985) Ornithodoros (Alectorobius) spheniscus Hoogstraal, Wassef, Hays & Keirans, 1985 Spheniscus humboldti, resting area and caves inhabited by the species, Peru (Hoogstraal et al 1985); unspecified site of infection, Chile (González-Acuna et al 2008b) Ornithodoros (Alectorobius) yunkeri Spheniscus mendiculus, nest, Galapagos islands (Keirans 1984;Hoogstraal et al 1985, Dietrich et al 2010 Family Dermanyssidae Kolenati, 1859 Liponyssoides eudyptulae Fain & Holloway, 1993 Eudyptula minor, nest, New Zealand (Fain and Galloway 1993;Bishop and Heath 1998) Family Haemogamasidae Oudemans, 1939 Eulaelaps sp.…”
Section: Unidentified Anisakid Larvaementioning
confidence: 99%